HIV and aging: A primer for NPs. Issue 5 (May 2019) - Kwong, Jeffrey; Reyes, Darcel; Murphy, Nancy; Loveless, Thomas J.
Abstract : Abstract: Estimates indicate 70% of all individuals with HIV will be age 50 or older by 2030. Chronic conditions, including cardiovascular disease, diabetes mellitus, kidney disease, malignancies, neurocognitive disorders, and osteopenia or osteoporosis, occur more frequently in patients with HIV and have become the leading cause of morbidity in this population. NPs play an integral role in helping this population age healthfully. Abstract : Estimates indicate 70% of all individuals with HIV will be age 50 or older by 2030. Chronic conditions, including cardiovascular disease, diabetes mellitus, kidney disease, malignancies, neurocognitive disorders, and osteopenia or osteoporosis, occur more frequently in patients with HIV and have become the leading cause of morbidity in this population. NPs play an integral role in helping this population age healthfully.